A randomised study of two training programmes for general practitioners in the techniques of shoulder injection. Issue 10 (12th September 2003) - Gormley, G J; Steele, W K; Stevenson, M; McKane, R; Ryans, I; Cairns, A P; Pendleton, A; Wright, G D; Taggart, A J
Abstract : Objectives: To evaluate the impact of two different modes of shoulder injection training on the level of confidence and number of injections performed by general practitioners (GPs) Methods: Demographic details, and information on referrals for shoulder problems, shoulder joint injection activity, and confidence in the six months before training were obtained for 40 GP principals at baseline. Standardised training in the techniques of shoulder joint injection using rubber mannequins was given to all GPs. Twenty of these GPs were randomly allocated to receive additional training on patients in hospital joint injection clinics. Six months after both forms of training the shoulder injection and referral activities of all GPs were reassessed. Results: Both training groups had comparable demographic characteristics and baseline clinical activity. GPs who had additional training with patients reported a marked increase in their level of confidence in performing shoulder injections and the number performed. The number of shoulder referrals did not differ between the groups Conclusion: Training on patients in addition to conventional training on mannequins increased GPs' shoulder injection activity and their level of confidence. Hospital injection clinics may provide a suitable setting in which to train GPs interested in developing their shoulder joint injection skills.